Konstribusi Sains dalam Membangun Masyarakat Akademik yang Maju dan Berkelanjutan dalam Ruang Lingkup Mahasiswa Pendidikan Fisika Universitas Jember - Hamdani, Moch. Asrofi; Sari, Sindi Novita; Sari, Lintang Kurnia; Mahardika, I Ketut; sari, Erna; Handono, Sri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Science has played an important role in creating a progressive and sustainable society. The contribution of science to societal development covers various fields, including technology, health, environment, nutrition, energy and education. Through scientific methods and in-depth research, science provides a deeper understanding of the world around us and opens the door to innovation and progress. Science has also produced breakthroughs in the health sector, including vaccines, drugs, medical technology, and surgical procedures that more effective. In the environmental field, science has contributed to our understanding of the threats posed by climate change, pollution, and other environmental damage. Through research and innovation, science has contributed to solutions such as renewable energy, waste processing technology, and sustainable agricultural practices. By harnessing this scientific knowledge, society can respond to environmental challenges in a more sustainable way. In the energy sector, alleviating poverty by expanding access to knowledge has increased understanding of efficient and alternative energy use, including renewable energy sources and energy-saving technologies. Education is also an important contribution of science in building a progressive and sustainable society. Through the continuous development of science and the application of innovation, science plays an important role in shaping a society that is progressive, sustainable, and able to overcome complex global challenges